2022
DOI: 10.1177/23743735211069833
|View full text |Cite
|
Sign up to set email alerts
|

What Do You Want Us to Know?: Learning From Life Stories to Improve Veterans’ Healthcare Experiences

Abstract: My Life My Story (MLMS) is a national Veterans Health Administration (VA) life story interview program that aims to provide more humanistic care for veterans by focusing on the patient as a person. Our project took place at the Pittsburgh VA Healthcare System and had 3 main goals: (1) describe themes that emerge in MLMS interviews from the prompting question, what do you want your healthcare provider to know about you?; (2) identify topics of importance to veterans and suggest ways for healthcare providers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The medicalized environment in which stories were recorded may also serve to have Veterans emphasize particularly traumatic or life‐threatening medical experiences. This research builds on recent work that identified key themes in 17 Veteran MLMS narratives, including early hardships, facing mortality, and recounting harrowing combat experiences 27 . Although many Veterans may have opted not to disclose such experiences, it appears that a large number do wish for their medical team to know about their experiences confronting past adversity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The medicalized environment in which stories were recorded may also serve to have Veterans emphasize particularly traumatic or life‐threatening medical experiences. This research builds on recent work that identified key themes in 17 Veteran MLMS narratives, including early hardships, facing mortality, and recounting harrowing combat experiences 27 . Although many Veterans may have opted not to disclose such experiences, it appears that a large number do wish for their medical team to know about their experiences confronting past adversity.…”
Section: Discussionmentioning
confidence: 97%
“…This research builds on recent work that identified key themes in 17 Veteran MLMS narratives, including early hardships, facing mortality, and recounting harrowing combat experiences. 27 Although many Veterans may have opted not to disclose such experiences, it appears that a large number do wish for their medical team to know F I G U R E 1 Fifteen most potentially traumatic events, adverse childhood experiences and additional life challenges found in Veteran narratives containing a disclosure about their experiences confronting past adversity. This finding calls on clinicians to become more competent in responding to trauma disclosures.…”
Section: Discussionmentioning
confidence: 99%